Research on Heat Distribution Law of Machine Tool Spindle Bearing Components Including Thermal Deformation and Thermal Displacement - Chen Feifan; Qiu Ming; Dong Yanfang; Lu Tuanliang; Chen Lihai (Jixie chuandong)
Accurate prediction of the temperature field of machine tool spindle bearings can determine the service condition of the bearings and lay the foundation for bearing operation and maintenance. By considering the dynamic effects of radial thermal deformation and axial thermal displacement on the internal geometry of the bearing, the pseudo-statics model is modified, and on the basis of the partial method of calculating the overall frictional heat generation of the bearing, a coupled analysis model of the composite deformation and temperature field of the spindle system components is established in combination with the thermal network method. In turn, the bearing temperature rise curves with variable heat distribution under different working conditions are solved, as well as the ratio of the steady-state heat of the bearing assembly under the corresponding conditions. The results show that in the working state of the spindle bearing, the heat generation of the inner raceway is generally higher than that of the outer raceway; with the change of spindle speed and axial force, the heat generation of bearing assembly will change according to a certain rule.